Role of personal factors in perception of workplace bullying among telecommunication personnel - Aneeza Bashir; Rubina Hanif; Masood Nadeem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Workplace bullying is a substantial and intricate issue that presents a target for organizations to cope. The present study is cross-sectional survey that examined the role of personality traits (extroversion, conscientiousness, emotional stability, agreeableness, and openness to experience) of individuals and demographics (i.e., gender, marital status, education and monthly income) in their perception of workplace bullying. Negative Acts Questionnaire (Einarsen & Raknes, 1997) and Mini Markers Personality Inventory (Saucier, 1994) were administered on a sample of (N = 280; women = 83, men=197, Age range from 20 to 40 years) employees of five telecommunication companies from Islamabad. Results showed that negative correlation exist between personality traits (extroversion agreeableness, emotional stability and conscientiousness) and workplace bullying. Agreeableness, conscientiousness, and emotional stability are significantly predicting workplace bullying. Non-significant differences were revealed on gender, marital status, income level, job experience and education with respect to workplace bullying. The findings are discussed in cultural context. This study has utilized a crosssectional design, rather than a longitudinal design. The sample of the study was small and only limited to the cellular services providing companies. Future researches should include a larger sample from other professions.
Keywords: 330; Workplace bullying; extroversion; conscientiousness; emotional stability; agreeableness; openness to experience